Do the reciprocal trust less? - Steffen Altmann; Thomas Dohmen; Matthias Wibral (Institute for the Study of Labor (IZA), 2007)
We study the intrapersonal relationship between trust and reciprocity in a laboratory experiment. Reciprocal subjects trust significantly more than selfish ones. This finding raises questions about theories of social preferences which predict that fairer players should trust less.
Keywords: 330; Vertrauen; Gerechtigkeit; Soziale Wohlfahrtsfunktion; Soziales Verhalten; Test